2016
DOI: 10.11005/jbm.2016.23.4.215
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Fatty Degeneration of Thigh Muscles Measured by Computed Tomography in Hip Fracture Patients

Abstract: BackgroundRecently, as an independent fracture factor from Bone mineral density (BMD), muscle weakness due to the fatty degeneration of thigh muscles have been attracting attentions as causes of hip fracture. The purpose of this study is to investigate the correlation between the body composition and BMD and fatty degeneration of thigh muscles of the female patients over 65 years old with osteoporotic hip fracture.MethodsThis study was conducted with 178 female osteoporotic hip fracture patients. Total hip BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…We also observed in obese older women that mid-calf muscle density was positively associated with proximal tibial cortical vBMD and area (B=2.91 mg/cm 3 ; 95% CI 0.02, 5.80 and 2.71 mm 2 ; 0.06, 5.33, per mg/cm 3 higher muscle density, respectively) (16). A study of 178 osteoporotic women with hip fractures has further demonstrated that gluteus maximus (r=0.230) and abductor (r=0.221) muscle densities are positively correlated with hip BMD (14). It should be noted that the apparent effect sizes for associations between mid-calf muscle density and tibial bone parameters, whilst significant, were small in the present study; for example, the mean cortical vBMD value at the proximal tibia was 1089 mg/cm 3 , and a 1 mg/cm 3 higher muscle density was associated with only 1.4 mg/cm 3 higher cortical vBMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed in obese older women that mid-calf muscle density was positively associated with proximal tibial cortical vBMD and area (B=2.91 mg/cm 3 ; 95% CI 0.02, 5.80 and 2.71 mm 2 ; 0.06, 5.33, per mg/cm 3 higher muscle density, respectively) (16). A study of 178 osteoporotic women with hip fractures has further demonstrated that gluteus maximus (r=0.230) and abductor (r=0.221) muscle densities are positively correlated with hip BMD (14). It should be noted that the apparent effect sizes for associations between mid-calf muscle density and tibial bone parameters, whilst significant, were small in the present study; for example, the mean cortical vBMD value at the proximal tibia was 1089 mg/cm 3 , and a 1 mg/cm 3 higher muscle density was associated with only 1.4 mg/cm 3 higher cortical vBMD.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism by which low skeletal muscle density may influence fracture risk in older adults is through its associations with bone health. Lower gluteus maximus and abductor muscle densities are associated with lower hip areal bone mineral density (aBMD) in hip fracture patients (14), and measures of 'bone qualities', such as peripheral volumetric BMD (vBMD) and bone geometry (15), also appear to be poorer in those with lower muscle density. Indeed, we recently reported that lower mid-calf muscle density is associated with lower proximal tibial cortical vBMD and area in older adults (16), and high relative lower-leg intra-muscular fat has also been associated with lower tibial bone content and area (17).…”
Section: Introductionmentioning
confidence: 99%
“…fat Pure muscle 60 Internal calibration – psoas muscle of young healthy individuals Mühlberg 2017 [25] Pure adipose tissue ≈ −100 Internal calibration – thigh subcut. adipose tissue HDM 35 Internal calibration – psoas muscle of young healthy individuals Hahn 2016 [106] Muscle 30 to 80 Fat −190 to −30 HDM = high-density muscle; LDM = low-density muscle; NDM = normal-density muscle; subcut. = subcutaneous.…”
Section: Methods Of Quantitative Ct Imagingmentioning
confidence: 99%
“…These descriptors predicted hip fracture with a hazard ratio (HR) of up to 1.6 that remained significant after adjustment for aBMD of the spine and total hip (HR up to 1.2) [30] , but areal total hip BMD alone resulted in an HR of 2.1 for hip fracture prediction. The other two studies [106] , [107] did not specifically target hip fracture prediction or discrimination.…”
Section: Applications Of Quantitative Muscle Imaging By Ctmentioning
confidence: 99%
“…The range of CT values was set to 30 to 80 HU to determine the muscle tissue and select part of the psoas major (Fig. 2) 13 . CSAs of the psoas major muscle on the approach and contralateral sides were measured using the axial CT view at the level of the surgical intervertebral space preoperatively and postoperatively at 1 week and 3, 6, and 12 months.…”
Section: Assessment Of the Muscle Volume Of The Psoas Majormentioning
confidence: 99%